The birth of the national renaissance in modern Albanian political discourse - Kola, Muhamet (My University, 2020)
The study of the genealogy of Albanian nationalism has created the illusion among Albanian scholars that it may weaken their patriotism, which could endanger Albania as a nation. Therefore, many foreign scholars have taken up the study of the birth of Albanian nationalism, since amongst Albanian scholars its study is still considered a taboo. This taboo is related to the fear of the truth which may reveal the origin and the way the historical myths presented to Albanians were created. That is why one of the aims of this study is to analyze how Albanian national consciousness is constructed. Albanian nationalist discourses began to come to existence in the 19th century through attempts to create a standardized national language, national newspapers, and various national works by Albanian intellectuals of the period. The Albanian intellectuals who tried to create Albanian national sentiments are considered to be representatives of the Albanian National Renaissance. The problem that this thesis deals with consists of the deconstruction of the argument that many scholars of Albanian nationalism uphold that it arose as an internal social consequence or as it can be better put, as a consequence of the demand of Albanian society for the creation of nationalism. For this reason, another purpose of this study is to establish the hypothesis that Albanian nationalism was not constructed as a consequence of society's demand for such a change but its construction was imposed by Renaissance intellectuals on Albanian society as an urgent need because of the geopolitically threatening reality. The methodology used in this study is of a qualitative nature, consisting of analyzing the works of some of the predominant representatives of the Albanian intellectual elite who were involved in the creation of Albanian nationalism. Since the ways in which Albanian nationalism was constructed required descriptive interpretation, the hermeneutic circle method together with the text analysis method was used.

Arnavut milliyetçiliğinin şeceresinin incelenmesi, Arnavut alimler arasında vatanseverliği zayıflatabileceği ve Arnavutluk'un bir millet olarak ortadan kaybolmasını tehlikeye sokabileceği yanılsamasını yaratmıştır. Arnavut bilginlerin arasında yaptığı çalışma hala tabu olarak kabul edilirken, pek çok yabancı bilgin Arnavut milliyetçiliğinin doğuşunu ele aldı. Bu tabu gerçeği öğrenme korkusuyla ilgilidir. Gerçek, kökeni ve tarihi mitlerin yaratılma şeklini ortaya çıkarabilir. Bu çalışmanın amacı Arnavutluk milli bilincinin nasıl inşa edildiğini analiz etmektir. Arnavut milliyetçi söylemlerin başlangıcı 19. yüzyılda ortaya çıkmaya başlamıştır. Arnavut entelektüellerinin standartlaştırılmış bir ulusal dil oluşturma girişimleri, ulusal gazeteler ve çeşitli ulusal çalışmalarla milliyetçi söylemleri başlatmıştır. Arnavutluk milli duygusunu yaratmaya çalışan Arnavut aydınları, Arnavutluk Ulusal Rönesans'ının temsilcileri olarak kabul edilmektedir. Bu tezin nihai hedefi de milliyetçiliğin içsel bir sosyal sonuç ya da Arnavut toplumunun milliyetçilik yaratma talebinin bir sonucu olarak ortaya çıktığı argümanını ortadan kaldırmaktır. Bu nedenle bu çalışmanın alt amacı, Arnavut milliyetçiliğinin toplumun böylesi bir değişim talebinin bir sonucu olarak inşa edilmediğini, ancak yapımının jeopolitik tehdit nedeniyle acil bir ihtiyaç olarak Rönesans aydınları tarafından getirildiği hipotezini oluşturmaktır. Bu çalışma nitel yöntemle ele alınmıştır. Arnavut milliyetçiliğinin oluşumunda yer alan, Arnavut entelektüel elitlerin bazı baskın temsilcilerinin çalışmalarını analiz etmekten ibarettir. Arnavut milliyetçiliğinin inşa edilme biçimlerinin betimleyici bir yorum gerektirdiği için metin çözümleme yöntemiyle hermenötik daire yöntemi kullanılmıştır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Arnavut milliyetçiliği; Tarihsel efsaneler; Ulusal duyarlılık; Albanian nationalism; Historical myths; National sentiment